A wholesale electricity market design sans missing money and price manipulation. (November 2019) - Woo, C.K.; Milstein, I.; Tishler, A.; Zarnikau, J.
Abstract: Using reliability differentiation via tolling agreements with diverse heat rates and fuel types, we propose an efficient wholesale electricity market design under demand and supply uncertainty. Mainly based on North America's market experience, our proposed design adopts an independent system operator's (ISO's) existing practice of least-cost dispatch of heterogeneous generation units, real-time energy price determination and capacity rationing. It solves the missing money problem of inadequate incentive for thermal generation investment, without requiring the ISO to operate centralized capacity auctions, make capacity payments, set high energy price caps, or subsidize market entry. It preempts independent power producers' price manipulation in the ISO's real-time market for energy, thus easing the ISO's burden of market monitoring. It suggests two-part pricing of end-use consumption and power demand of a load serving entity's retail customers, thus meaningfully linking the wholesale and retail markets. It is applicable to countries that have implemented wholesale competition or are in the process of doing so. Hence, its policy implication is that it should be considered in the ongoing debate of electricity reliability and market competition. Highlights: Develop a new market design for wholesale electricity competition. Document the design's solution for missing money and price manipulation. Document the design's efficient planning, pricing and operation. Document the design's practical implementation. Recommend the design for reliability differentiation and market competition.